The chemical constituents of Ellipeia cuneifolia and their antibacterial activity - Hasliza Yusof,; Laily Din,; Wan A. Yaacob,; Nazlina Ibrahim,; Bohari M. Yamin,; A. Latiff, (Universiti Kebangsaan Malaysia, 2015)
Chromatographic purification of chloroform extract of the twigs of Ellipeia cuneifolia has led to the discovery of three compounds comprising of 2´,4´-dihydroxy-4,6´-dimethoxychalcone; tepanone; and O-methylmoschatoline. Structures of the compounds were established by interpreting their spectral data and by comparing them with those of the literature. Two of them showed antibacterial activities.